Pengaruh Budaya Organisasi, Disiplin Kerja, dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Penajam Paser Utara - Tamzil Yusuf; Tutik Yuliani; Tirani Ulik Nur Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of organizational culture, work discipline, and work environment on job satisfaction among employees of the Civil Service and Human Resource Development Agency in Penajam Paser Utara Regency. A quantitative descriptive method was used, with total sampling of 44 employees consisting of civil servants and government contract employees. Data collection was conducted through literature review, interviews, and questionnaires based on a Likert scale. Data analysis was performed using SEM-PLS with Smart-PLS and SPSS applications. The outer model was tested for construct validity and reliability, while the inner model measured relationships between variables using R-square values and t-statistic hypothesis testing. Results indicated composite reliability and Cronbach's Alpha values above 0.70, demonstrating good reliability. The R-square value of 0.729 showed that job satisfaction was influenced by organizational culture, work discipline, and work environment by 70.9%. Hypothesis testing showed that organizational culture, work discipline, and work environment significantly affected job satisfaction with p-value < 0.05. Based on the findings, it is recommended to enhance organizational culture, work discipline, and work environment to improve employee job satisfaction.